The impact of the interest rate changes on the performance of automobile sector in Malaysia / Mohamed Zaidi Mat Zain - Mat Zain, Mohamed Zaidi (2002)
The impact of the interest rate changes on the performance of automobile sector in Malaysia. The focus will be on the impact of interest rate changes on the performances of automobile sectors and how thcy survive when facing the interest rate fluctuation over the year in Malaysia. The rate of interest is the key economic variable, which materially affects the purchasing power of coporate and individual in Malaysia. A change in interest rate has an important implication for the economic smooth running. Due to the fact that the changes in the interest rate affect the customers' reaction as well as business decisions. The main challenge for those involving in the financial and business planning is to be foreseeing the after effect of the interest rates changes in the country. Nevertheless, the changes of interest rates in Malaysia can be quite political as Government (Bank Negara Malaysia) does play a major role in determining the level of interest rates for the country.